Performance Evaluation of Carbon Block Electrodes in a Dual-Chamber Microbial Fuel Cell Using Rice Paddy Sludge for Bioelectricity Generation - Septiana Ambarwati; Henny Parida Hutapea; Ameilia Wahyu Banuwati; Sri Jangkung Laksono Sukardi (Universitas Islam Raden Rahmat, Malang, 2026)
Microbial Fuel Cell (MFC) are a promising technology for converting organic biomass into renewable electricity through the activity of electroactive microorganisms. Rice paddy sludge is an abundant biomass resource containing organic matter and naturally occurring electroactive microorganisms, making it a potential substrate for sustainable bioelectricity generation. This study developed a dual-chamber MFC using carbon block electrodes and rice paddy sludge as both the substrate and microbial inoculum. After three days of operation, the system produced a maximum voltage of 0.22 V. Under an external resistance of 1000 Ω and a total anodic surface area of 0.02 m², the calculated power output and power density were 0.0484 mW and 2.42 mW/m², respectively. These findings demonstrate that rice paddy sludge can generate bioelectricity in MFC systems. Although the power density was lower than that reported for modified electrodes, carbon block electrodes provide advantages such as low cost, availability, and durability, highlighting their potential for sustainable MFC applications.